Unconventional Extraction of Total Non-Polar Carotenoids from Pumpkin Pulp and Their Nanoencapsulation - Nicola Pinna; Federica Ianni; Francesca Blasi; Arianna Stefani; Michela Codini; Stefano Sabatini; Aurélie Schoubben; Lina Cossignani (Molecules, 2022)
Pumpkin is considered a functional food with beneficial effects on human health due to the presence of interesting bioactives. In this research, the impact of unconventional ultrasound-assisted extraction (UAE) and microwave-assisted extraction techniques on the recovery of total non-polar carotenoids from Cucurbita moschata pulp was investigated. A binary (hexane:isopropanol, 60:40 v/v) and a ternary (hexane:acetone:ethanol, 50:25:25 v/v/v) mixture were tested. The extracts were characterized for their antioxidant properties by in vitro assays, while the carotenoid profiling was determined by high-performance liquid chromatography coupled with a diode array detector. UAE with the binary mixture (30 min, 45 °C) was the most successful extracting technique, taking into consideration all analytical data and their correlations. In parallel, solid lipid nanoparticles (SLN) were optimized for the encapsulation of the extract, using β-carotene as a reference compound. SLN, loaded with up to 1% β-carotene, had dimensions (~350 nm) compatible with increased intestinal absorption. Additionally, the ABTS ((2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) assay showed that the technological process did not change the antioxidant capacity of β-carotene. These SLN will be used to load an even higher percentage of the extract without affecting their dimensions due to its liquid nature and higher miscibility with the lipid with respect to the solid β-carotene.